RECLAIMING HERITAGE UNDER EMPIRE: THE FOUNDING OF SONOBUDOYO MUSEUM AS A SITE OF CULTURAL NEGOTIATION AND SYMBOLIC DECOLONIZATION - Fahmi, Rezza Fauzi Muhammad; Farid, Mahmud; Razy, Mohammad Refi Omar Ar; Assondani, Muhammad Mufti Najmul Umam (The Indonesian Journal of Social Studies, 2025)
This article examines the founding of the Sonobudoyo Museum in 1935 as a form of indigenous cultural articulation within a space still governed by colonial power. Using historical methods and a postcolonial theoretical framework, the study draws upon primary sources from Djåwå journal archives and secondary literature on colonial museology, cultural nationalism, and tropical architecture. The findings indicate that while conceived within colonial frameworks, the museum served as a site of symbolic negotiation that enabled expressions of local cultural agency through traditional architectural forms, indigenous curatorial practices, and the active involvement of local rulers. The museum not only inherited the failures of a previous 1885 museum project but also served as a symbolic corrective. As such, Sonobudoyo represents a “third space” where cultural identity was hybridized and rearticulated at the intersection of colonial structures and local emancipatory aspirations.